Tradução comentada de A caçada de Lygia Fagundes Telles: uma proposta estrangeirizante - Presotto, Bianca (2021)
This paper presents a commented translationproposalfor the short story ACaçada(2009) by LygiaFagundesTelles into English, bringingreflections that involved this process regarding to Translation Studies and the analysis of fantastic construction in the source text and in the target text. The main objective of this study was to elaborate a translation into the English language that was mainly foreignizing, so that the produced text would leave residues of the source text according to the perspective valued by Venuti (1995; 2002). The objectives are: a) investigateTelles’life and work in order to investigate her developmentas a writer, her literaryinfluences andliterary aesthetics; b) map Telles’ translations already published inliterary polysystemsthat are beyond the Brazilian polysystemin order to verify the author’s representation overseas;c) identify which translation tendencies were carried by the translator, in order to expose her choices and to verify which challenges were found duringthe construction of a foreignizing translation for the Portuguese-English language pair; and d) carry out an analysis of the semantic chain of both the source text and the target text, in order to verify how the fantastic configuration in the target text took place regarding the thematic axes of fearand space. Concerning methodology, this study consists of an introspective and retrospectiveresearch(FRASER, 1996), since the commented translation consists of translating and reflectingon this process. Ina broad scope, this research relies onthe Polysystem Theory according to the perspective of Even-Zohar (1980); during the production of the translation, Venuti’s (1995; 2002) foreignizing translation perspective was followed; and for the analysis of translation procedures, Berman (2013) and Lanzettiet al.(2009) studies were taken into account. Regarding fantastic construction analysis, Roas’ (2014) precepts were used to present a general scenery of the fantastic genre; Freud (2010) and his concept of unheimlichwas taken into account; and Todorov’s (1980) to include the concept ofhesitation. As for the analysis of the semantic chain, Berman (2013) and Paganine (2011) support the analysis of signifiers chains of spaceand fear. For the analysis of these two axes, the studies of Borges Filho (2007) and Menon (2013) were used. The results obtained in this study indicate the production of a translation that exhibits manifestations of foreignizing strategies, in which the translator has chosento leave marks from the foreign in terms of text structural, stylistical and cultural elements throughout the translation process. Having said that, it was also found that the translation maintained features of Telles’ writing in order to keep the expressiveness of language so as to maintain the element of the fantastic in the target text and suggest to English language readers that the target text comes from a culture that is different from that of the reader. Thus, it was possible to develop a commented translation of Telles’ short story, making this tale available in English language, and in turn, value Brazilian national literature and contribute to the growth and valuation of Translation Studies in Brazil.